2021
DOI: 10.1021/jacs.1c04367
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Formal Vinylogous N–H Insertion of Secondary Aliphatic Amines Catalyzed by a High-Spin Cobalt(II) Complex

Abstract: Vinylcarbene insertion into the nitrogen–hydrogen (N–H) bond of amines allows direct access to α,β-unsaturated γ-amino acid derivatives, meeting a marked challenge in the control of regio- and enantioselectivities. Here, we report a highly γ-selective and enantioselective insertion into N–H bonds of aliphatic or aromatic secondary amines with vinyl substituted α-diazo pyrazoleamides using a high-spin chiral N,N′-dioxide/cobalt­(II) complex catalyst. The method affords a wide variety of valuable optically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…Firstly, the diazo bound Co II intermediate Int1 was considered as a reactive species for the following investigations [10g, 11] . We examined two pathways by which the release of N 2 possibly takes place through either doublet or quartet transition state [11e] . The results show that the quartet state pathway is much more favorable than the doublet pathway, yielding a spin crossover product Co(ΙΙ) carbene species Int2 D .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the diazo bound Co II intermediate Int1 was considered as a reactive species for the following investigations [10g, 11] . We examined two pathways by which the release of N 2 possibly takes place through either doublet or quartet transition state [11e] . The results show that the quartet state pathway is much more favorable than the doublet pathway, yielding a spin crossover product Co(ΙΙ) carbene species Int2 D .…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations were performed using Gaussian software (see the Supporting Information for more details). Previously, we showed that a 1-acrylpyrazole-bound Co­(II) complex is a stable species . As such, the complex Int1 was considered as a reactive species for the SKI addition (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The catalytic carbene insertion into NÀ H bonds has attracted much attention because it provides various bioactive molecules such as α-amino acid derivatives and α-amino ketones. [3,13] Our investigations on the catalytic application of complexes IV-VIII were started on carbenoid NÀ H insertions by using αdiazoacetate 1 a and aniline 2 a at room temperature with 2 mol% of catalyst (Table 1). The catalytic carbenoid NÀ H insertions by complexes IV-VIII all worked well, with VI demonstrating the highest catalytic activity (entries 1-5).…”
Section: Catalytic Carbene Insertion Into N-h Bondsmentioning
confidence: 99%
“…Transition-meta-catalyzed carbene migratory insertion into CÀ H or XÀ H bonds is a powerful tool for the construction of CÀ C and CÀ X bonds. [1] In the past few years, many types of XÀ H insertions including OÀ H, [2] NÀ H, [3] SÀ H, [4] SiÀ H [5] and recently emerged BÀ H [6] bonds have been realized with different carbene precursors [7] and catalysts. Despite much progress have been made in this type of reaction, in view of its great utility and wide application, the development of new highly efficient and selective catalysts is still in demand.…”
Section: Introductionmentioning
confidence: 99%